Theoretical study on the reaction mechanisms of Michael chirality addition between propionaldehyde and nitroalkene catalyzed by an enantioselective catalyst. Issue 6 (2nd April 2018) - Zhou, Xinming; Li, Ling; Sun, Xuejun; Wang, Yajun; Du, Dongmei; Fu, Hui
Abstract: The asymmetric Michael addition between propionaldehyde and nitroalkene catalyzed by 8‐(ethoxycarbonyl)‐1, 2, 3, 3a, 8, 8a‐hexahydropyrrolo[2, 3‐b]indole‐2‐carboxylic acid has obtained relatively high yields and excellent enantioselectivities at room temperature. In this study, the molecular structures and optical activity of the most stable conformation I are optimized at B3LYP/6‐311++ G(d, p) level. We find that levorotatory conformation I catalyzing the same Michael addition can produce laevo‐product A and dextrorotatory conformation I′ can obtain the dextral‐product A'. These results have guiding significance for further studying on the new chemzymes and the mechanism of the obtained different chiral products. Abstract : The figure describes the optimized structures of catalyst I and its mirrorimageisomer I′, product A and its enantiomer product A'. In this study, the molecular structures and optical activity of the most stable conformation I are optimized at the B3LYP/6‐311++G(d, p) level, and it is a chiral molecule. To research on the effect of the reaction mechanisms and chirality on Michael addition between propionaldehyde and nitroalkene catalyzed by an enantioselective catalyst, we roll over I to get its mirrorimageisomer I′. We find that levorotatory conformation I catalyzing the same Michael addition can produce laevo‐product A and dextrorotatory conformation I′ can obtain the dextral‐product A'.